Design, synthesis and evaluation of a series of potential prodrugs of a Bruton's tyrosine kinase (BTK) inhibitor - Zhou-Peng Xiao; Min Liao; Xue-Juan Huang; Yu-Tong Wang; Xiao-Cui Lan; Xue-Ying Wang; Xi-Tao Li (Frontiers Media S.A., 2023)
BTK has become a particularly attractive therapeutic target in autoimmune diseases and B-cell malignancies, making BTK inhibitors a valuable and important therapeutic option. We present the design, synthesis, and evaluation of a series of prodrugs of a BTK inhibitor with an insoluble 2,5-diaminopyrimidine structure. Tails containing different solubilizing groups were added to the parent molecule via an ester linkage. Prodrug 5a showed good aqueous solubility and could be efficiently converted to the parent in a human plasma stability study. The rational prodrug design was supported by molecular studies and a dramatically reduced BTK kinase-inhibitory potential. Taken together, the chemical, biological, and molecular studies suggest that prodrug derivatization of the 2,5-diaminopyrimidine scaffold could be a potential strategy for advancing this series of BTK inhibitors into the therapeutic arena.